Salivary C-Reactive Protein in Hashimoto's Thyroiditis and Subacute Thyroiditis - Nivedita L. Rao; Sukanya Shetty; Krishnaraj Upadhyaya; Prasad R. M; Eric C. Lobo; H. P. Kedilaya; Ganesh Prasad (International Journal of Inflammation)
C-reactive protein (CRP), an acute-phase reactant, has been identified as a saliva-based biomarker of inflammation. The objective of the study was to estimate and compare salivary CRP levels in Hashimoto's thyroiditis (HT) and Subacute thyroiditis (SAT). The study included 30 HT patients who presented with clinical features of hypothyroidism, 15 SAT patients who presented with clinical features of hyperthyroidism, and 20 healthy age- and sex-matched euthyroid controls. CRP levels in saliva were estimated using an Enzyme-Linked Immunosorbent Assay method with enhanced sensitivity. In HT, the mean salivary CRP levels did not differ significantly from controls. SAT patients had significantly elevated salivary CRP levels compared to HT patients and controls. The rise in salivary CRP levels in SAT patients conceivably reflects the presence of an inflammatory process. Saliva CRP levels appear to serve as inflammatory markers in SAT patients and may aid their clinical evaluation.